Female Masculinity and Power Relation in Patriarchic System: Case Study Tomboyism of Bacha Posh in Afghanistan - Padmi, Made Fitri Maya (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
The biological/essentialist theory of gender assumes that biological sexes determine the behavior patterns and roles of males and associates them with masculinity and females and associates them with femininity. However, there is debate to determine whether genders are biological or socially and culturally constructed. Feminist critique of the power relation between masculinity and femininity defined as the power to give privilege to the position of masculinity and men, and acknowledge the subordination of femininity and women. People also guided to conform to gender norms in society as identity. Female masculinity emerged as part of a resistance to the gender norms where females should adopt and perform feminine values and ways of life. This paper analyze the position of female masculinity, which is distinct from masculinity in patriarchic systems. This paper also analyze the early stage of female masculinity, tomboyism called Bacha Posh as experienced by many girls in Afghanistan. This paper showed to us that the phenomena of Bacha Posh reflect the gender trait was not flexible. It was decided by the need to fulfill patriarchy system in Afghan society.